2018
DOI: 10.1186/s13023-018-0903-6
|View full text |Cite
|
Sign up to set email alerts
|

A health state utility valuation study to assess the impact of treatment mode of administration in Gaucher disease

Abstract: BackgroundThis study aimed to obtain UK societal-based utility values for health states related to treatment mode of administration using Gaucher disease as the background condition.MethodsA review of relevant literature and expert clinical input informed the development of five health states characterising the impact of Gaucher disease and its management on patients’ lives. A base-state characterising the “controlled disease” was developed as well as four subsequent health states which varied in description o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 29 publications
(30 reference statements)
0
10
0
Order By: Relevance
“…Of importance, over half of our young adult sample was taking oral eliglustat at the time of data collection, while in earlier studies participants were exclusively treated with ERT. This distinction is noteworthy since recent research has suggested that treatment with oral eliglustat offers important advantages for quality of life (e.g., Hadi et al, ; Sechi et al, ). In our study, young adults who were taking eliglustat described improvement in their symptoms and their quality of life.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of importance, over half of our young adult sample was taking oral eliglustat at the time of data collection, while in earlier studies participants were exclusively treated with ERT. This distinction is noteworthy since recent research has suggested that treatment with oral eliglustat offers important advantages for quality of life (e.g., Hadi et al, ; Sechi et al, ). In our study, young adults who were taking eliglustat described improvement in their symptoms and their quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment with ERT has been associated with significant symptom reduction and improvement in HRQoL across a variety of domains. Some researchers have suggested that treatment with SRT offers benefits for quality of life relative to ERT due to greater convenience associated with oral versus intravenous administration (e.g., Elstein et al, ; Hadi, Swinburn, Nalysnyk, Hamed, & Mehta, ; Sechi, Dardis, & Bembi, ). Despite treatment however, patients with GD1 report persistent difficulty coping with the diagnosis, adverse effects of pain on daily activities, mood changes and anxiety, and a negative outlook on life (Packman, Crosbie, Behnken, Eudy, & Packman, ).…”
Section: Introductionmentioning
confidence: 99%
“…45,46,48,61 As with AEs, the vignette approach can isolate the utility impact of a specific treatment process attribute by holding all aspects of a health state constant except for this attribute. Process utilities estimated with vignettes have been included in CUAs conducted for HTA submissions, 38,41,62 and favorable HTA impressions of costeffectiveness suggest that these process utilities can be useful model inputs. [63][64][65][66]…”
Section: Treatment Process Utilitiesmentioning
confidence: 99%
“…The EQ-5D-5L is a measure of health that covers five dimensions-mobility, self-care, usual activities, pain/discomfort, and anxiety/depression-using five levels of severity-no, slight, moderate, severe, and extreme problems/unable to [16]. The measure describes 3125 health states (5 5 = 3125) and is used across many healthcare settings. A misery score can be calculated by summing the dimension-level responses for a crude estimate of health state severity ranging from 5 to 25.…”
Section: Measure Of Healthmentioning
confidence: 99%
“…The TTO is often used to elicit preferences for health states in the development of value sets for measures of health like the EQ-5D [2,3]. Because the TTO can be difficult to understand, valuation studies using the TTO have historically been conducted using resourceand time-intensive face-to-face studies to ensure respondent comprehension [4,5].…”
Section: Introductionmentioning
confidence: 99%